Kecenderungan Perilaku Narsistik pada Calon Legislatif - Ernida Marietha Manurung (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This research intended to find out the narsistic tendency behavior on the legislative candidates, clinically and socially, during the campaign or doing the socialization. This research was used qualitative approach. This research used two respondents who nominated themselves as the legislative candidates in the Legislative Election in 9th of April 2009. The collecting data method used was indepth interview and observation. The result of this research showed that narsistic indication behavior of legislative candidates was a part of narsistic personality disorder. This narsistic behavior disorder could be seen from the over self-esteem and interpersonal trust in getting the society interests. This was seen from the ways of the two respondents in socializing their programs were always telling others about their performances, their dedications and their optimistic behavior to get society symphaty by giving social contribution and being active in some activities. Based on the efforts that had been done, they believed that their family, close friends and the society would choose them in the election in 9 th of April 2009.